2010
DOI: 10.1002/app.31994
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and ionic conductivity of nanocomposites: Polyelectrolyte systems

Abstract: The synthesis, diffraction patterns, thermal stability, and ionic conductivity properties of methacrylate-type polymers are analyzed here to assess their feasibility as polymer electrolytes. From the parent polymer, poly (N,N-dimethylaminoethylmethacrylate), herein labeled PDMAEMA, a protonated derivative was used to prepare polymer/Montmorillonite nanocomposites with various clay contents (1, 3, and 5 wt %). AC spectroscopy provided the ionic conductivity data for the polymers and clay-polymer nanocomposites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…Therefore, these composites PMBS‐4/C 12 SB‐MMT (3% and 5%) show intercalated morphologies (see below). Intercalated structures are self‐assembled, well‐ordered multilayered structures where the extended polymer chains are inserted into the gallery space between parallel individual silicate layers separated by 2–3 nm 22. In contrast, when organic MMT at 1% is added an exfoliated structure is mainly obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these composites PMBS‐4/C 12 SB‐MMT (3% and 5%) show intercalated morphologies (see below). Intercalated structures are self‐assembled, well‐ordered multilayered structures where the extended polymer chains are inserted into the gallery space between parallel individual silicate layers separated by 2–3 nm 22. In contrast, when organic MMT at 1% is added an exfoliated structure is mainly obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Layered silicate nanocomposites based on montmorillonite (MMT) treated with different kinds of surfactants, i.e. sulphobetaine and ammonia surfactants have been prepared and the nanostructure and properties contrasted with those obtained from untreated MMT using a protonated sample of poly(N,N‐dimethylaminoethylmethacrylate) 22. Low concentration of sulphobetaine surfactant favored exfoliation whereas high concentration and untreated MMT favored intercalation of the polymer chain in the nanoplates.…”
Section: Introductionmentioning
confidence: 99%
“…14 DMAEMA was purified by vacuum distillation (84 C/15 mmHg). 14 DMAEMA was purified by vacuum distillation (84 C/15 mmHg).…”
Section: Polymer Synthesismentioning
confidence: 99%
“…14 The results suggested that the dielectric properties were a function of morphology and prompted us to further investigate the influence of nanostructure on the thermal and viscoelastic properties of these materials. The PDMAEM matrix, its protonated polymer (PDMAEMH), and the nanocomposites based on PDMAEMH/MMT (PH/clay) have been studied using dielectric spectroscopy and by high resolution transmission electron microscopy (HRTEM) demonstrating exfoliation and intercalation morphologies as a function of the type of surfactant used.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the current availability of nanoparticles with well‐defined size and morphology different states of confinement can be achieved for polymer nanocomposites: (i) polymer chains constrained by nanoclay, (ii) polymer chains inside nanopores or nanocylinders, or (iii) inorganic nanoparticles and hybrids (i.e., silica, alumina, POSS, and so on) dispersed in a polymer matrix …”
Section: Introductionmentioning
confidence: 99%